Mechanical Properties for Buton Asphalt - Aggregates Mixes - Karami, Muhammad (Curtin University, 2016)
The objectives of this research are to study the effect on the resistant to permanent deformation and fatigue cracking of asphalt mixtures using granular Buton Rock Asphalt (BRA) modifier binder. The BRA modified binder was formed by replacing 10, 20 and 30% of the base binder C-170 with BRA natural binder. The results of this study show that BRA modified asphalt mixtures performed better than unmodified asphalt mixtures with regard to permanent deformation and fatigue cracking.